Pengembangan Ekonomi Masyarakat Melalui Diversifikasi Produk Olahan Nenas Desa Kualu Nenas - Mery Berlian; Rian Vebrianto; Zarkasih; Merry Siska; Rosmaina; Musa Thahir (Tasnim Journal for Community Service, 2020)
The Community Service Program is carried out based on the problems faced by pineapple MSMEs, namely: 1) lack of knowledge and skills of the community regarding the diversification of pineapple processing; 2) pineapple waste has not been utilized optimally; 3) market access to promote products is still very limited; and 4) unavailability of communication media such as marketing programs for marketing pineapple processed products. From several identified problems, it was formulated that the problem to be resolved in this activity was the MSME Empowerment Program through diversification of processed pineapple products. This community service activity is Participatory Action Research (PAR) carried out using a descriptive approach method. In this service the target is farmers and 12 active UKM in Kualu Nenas Village. The results of the dedication show that the farmers strongly agree with the existence of community service activities as an effort to develop the economy, especially in the development of the community's economy through diversification of processed pineapple products.